Comparison of Plasma Dynamics in Plasma Focus Devices PF1000 and PF400 (Journal of Nepal Physical Society, 2016)
In this work we have simulated two different sizes of plasma focus devices: PF400, a small sub-kJ plasma focus device in operation at the Atomic Energy Commission in Chile and PF1000, a 1 MJ device at the International Centre for Dense Magnetised Plasmas (ICDMP) in Warsaw, Poland. Our aim is to compare the plasma dynamics observed in two different sizes of the devices. We compare the experimentally obtained data with the data predicted from our numerical experiments using the Lee model code. It has been observed that the peak current of the total current waveform, pinch current calculated from total current, and neutron yield agree reasonably well with published experimental data, however, slight differences are found in other parameters.Journal of Nepal Physical Society Vol.3(1) 2015: 55-59